Syringe free vaccination with CAF01 Adjuvated Ag85B-ESAT-6 in Bioneedles provides strong and prolonged protection against tuberculosis. - Dennis Christensen (PLoS ONE, 2010)
Bioneedles are small hollow sugar based needles administered with a simple compressed air device. In the present study we investigate how incorporation of a subunit vaccine based on TB vaccine hybrid Ag85B-ESAT-6 adjuvated with CAF01 into Bioneedles affects its immunogenicity as well as its ability to protect against TB in a mouse model. The CMI response measured by IFN-γ and antigen specific CD4+ T-cells was, two weeks after the last vaccination, significantly lower in the group immunized with Bioneedle-incorporated vaccine compared to the conventional vaccine, using syringe and needle. However, at four, nine and 52 weeks after vaccination we observed similar high IFN-γ levels in the Bioneedle group and the group vaccinated using syringe and needle and comparable levels of antigen specific T-cells. Furthermore, the protective efficacy for the two vaccination methods was comparable and similar to BCG vaccination both six and 52 weeks after vaccination. These results therefore advocate the further development of the Bioneedle devises and applicators for the delivery of human vaccines.